Photosynthetic adaptation strategies in peppers under continuous lighting: insights into photosystem protection - Lanoue, Jason; St. Louis, Sarah; Little, Celeste; Hao, Xiuming (Frontiers in Plant Science, 2024)
Energy efficient lighting strategies have received increased interest from controlled environment producers. Long photoperiods (up to 24 h - continuous lighting (CL)) of lower light intensities could be used to achieve the desired daily light integral (DLI) with lower installed light capacity/capital costs and low electricity costs in regions with low night electricity prices. However, plants grown under CL tend to have higher carbohydrate and reactive oxygen species (ROS) levels which may lead to leaf chlorosis and down-regulation of photosynthesis. We hypothesize that the use of dynamic CL using a spectral change and/or light intensity change between day and night can negate CL-injury. In this experiment we set out to assess the impact of CL on pepper plants by subjecting them to white light during the day and up to 150 µmol m-2 s-1 of monochromatic blue light at night while controlling the DLI at the same level. Plants grown under all CL treatments had similar cumulative fruit number and weight compared to the 16h control indicating no reduction in production. Plants grown under CL had higher carbohydrate levels and ROS-scavenging capacity than plants grown under the 16h control. Conversely, the amount of photosynthetic pigment decreased with increasing nighttime blue light intensity. The maximum quantum yield of photosystem II (Fv/Fm), a metric often used to measure stress, was unaffected by light treatments. However, when light-adapted, the operating efficiency of photosystem II (ΦPSII) decreased and non-photochemical quenching (NPQ) increased with increasing nighttime blue light intensity. This suggests that both acclimated and instantaneous photochemistry during CL can be altered and is dependent on the nighttime light intensity. Furthermore, light-adapted chlorophyll fluorescence measurements may be more adept at detecting altered photochemical states than the conventional stress metric using dark-adapted measurements.